3 + (-5) + 8 + (-4)

= 2 +8+(-4)

=2+4

• 0

As all of them are having the same variables, we can see that they are having the same values.

But some of them are positive, while the others are negative so weea d the positive variables together first.

3mn+8mn=11mn

Now, we add the negative variables together.

(-5mn)+(-4mn)=-9mn

now we subtract 9mn from 11mn.

11mn-9mn=2mn

• 1

3mn+5mn

+-=-

=2mn+8mn=10mn

=10mn+(-4mn)=6mn

ans 6mn

• 1

3mn+( -5mn )+8mn+( -4mn)

3mn-5mn+8mn-4mn

-2mn+4mn

2mn ans

• 0

2mn guys use for brains

• 0

2mn

• 0

2mn

• 0

here the question is

so ATQ we have,

=3mn+(-5mn)+8mn+(-4mn)

=3mn-5mn+8mn-4mn

=(3-5+8-4)mn

=(-2+4)mn

• 0

2mn

• -1

3mn+(-5mn)+8mn+(-4mn)

First, we will add all the like expressions    [{3mn+8mn}+{(-5mn)+(-4mn)}]

=11mn+(-9mn)

Now simply add the result                              = {11 + (-9) } mn

= 2mn

Therefore, the result is 2mn.

• 0
3mn+(-5mn)+8mn-4mn
if we open the brackets, it'll be
3mn-5mn+8mn-4mn.
If we sort according to the values, then It'll be
​3mn+8mn-5mn-4mn. And finally.....  if we find the values
i.e,=11mn-9mn.
=2mn....

• 1
3mn+(-5mn)+8mn-4mn
if we open the brackets, it'll be
3mn-5mn+8mn-4mn.
If we sort according to the values, then It'll be
​3mn+8mn-5mn-4mn. And finally.....  if we find the values
/i.e,=11mn-9mn
=2mn....
• 0